Law Enforcement Against Illegal Parking Attendants as Perpetrators of Extortion Crimes With the Restorative Justice Method in the Jurisdiction of the Medan Sunggal Police - Yolla Veronica Sembiring; Yasmirah Mandasari Saragih; T. Riza Zarzani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Extortion by illegal parking attendants is very troubling to the community, especially motorists, and law enforcement should be carried out. Based on the description above, the author is interested in making the problem a research entitled Restorative Justice as an Approach in Law Enforcement Against Perpetrators of Extortion Crimes. This journal aims to describe and analyze the factors that cause the crime of extortion and the role of restorative justice as a method of law enforcement against the perpetrators of the crime of extortion. The research method used in this study is empirical juridical research. There are several factors that cause the occurrence of extortion crimes, namely economic, environmental, educational, lack of supervision and law enforcement and lack of legal awareness in the community. The Medan Sunggal Police enforce the law through alternative or restorative justice. Restorative justice is the settlement of criminal cases by involving the perpetrator, the victim, the perpetrator/victim's family, and other related parties to jointly seek a fair settlement by emphasizing restoration to the original state, and not retaliation.